Early prenatal use of a multivitamin diminishes the risk for inadequate vitamin D status in pregnant women: results from the Maternal-Infant Research on Environmental Chemicals (MIREC) cohort study. Issue 3 (3rd June 2021) - Weiler, Hope A; Brooks, Stephen P J; Sarafin, Kurtis; Fisher, Mandy; Massarelli, Isabelle; Luong, The Minh; Johnson, Markey; Morisset, Anne-Sophie; Dodds, Linda; Taback, Shayne; Helewa, Michael; von Dadelszen, Peter; et al.
ABSTRACT: Background: Reports on the adequacy of vitamin D status of pregnant women are not available in Canada. Objectives: The objectives of this study were to examine vitamin D status across pregnancy and identify the correlates of vitamin D status of pregnant women in Canada. Methods: Pregnant women (≥18 years) from 6 provinces (2008–2011) participating in a longitudinal cohort were studied. Sociodemographic data, obstetrical histories, and dietary and supplemental vitamin D intakes were surveyed. Plasma 25-hydroxyvitamin D (25OHD) was measured using an immunoassay standardized to LC-MS/MS from samples collected during the first ( n = 1905) and third trimesters ( n = 1649) and at delivery ( n = 1543). The proportion of women with ≥40 nmol/L of plasma 25OHD (adequate status) was estimated at each time point, and factors related to achieving this cut point were identified using repeated-measures logistic regression. Differences in 25OHD concentrations across trimesters and at delivery were tested a using repeated-measures ANOVA with a post hoc Tukey's test. Results: In the first trimester, 93.4% (95% CI: 92.3%–94.5%) of participants had 25OHD ≥40 nmol/L. The mean plasma 25OHD concentration increased from the first to the third trimester and then declined by delivery (69.8 ± 0.5 nmol/L, 78.6 ± 0.7 nmol/L, and 75.7 ± 0.7 nmol/L, respectively; P < 0.0001). A lack of multivitamin use early in pregnancy reduced the odds of achieving 25OHD ≥40 nmol/L (ORadj = 0.33; 95% CI: 0.25–0.42) across all time points. Factors associated with not using a prenatal multivitamin included multiparity (ORadj = 2.08; 95% CI: 1.42–3.02) and a below-median income (ORadj = 1.39; 95% CI: 1.02–1.89). Conclusions: The results from this cohort demonstrate the importance of early multivitamin supplement use to achieve an adequate vitamin D status in pregnant women.